Odpowiedź:
[tex]4 : \frac{1}{2} - \frac{14}{3} * \frac{9}{7} = 2 - 2 * 3 = 2 - 6 = -4\\\\[/tex]
[tex]6 \frac{1}{3} * (\frac{2}{3}+\frac{3}{4}) = 6\frac{1}{3} * (\frac{8}{12} + \frac{9}{12}) = 6\frac{1}{3} * \frac{17}{12} = \frac{19}{3} * \frac{17}{12} = \frac{323}{36} = 8\frac{35}{36}\\[/tex]
[tex]\\(\frac{2}{3} + \frac{5}{6}) * 3 - (\frac{7}{9}-\frac{1}{2}) = \frac{3}{2} * 3 - \frac{5}{18} = \frac{9}{2} - \frac{5}{18} = \frac{38}{9} = 4\frac{2}{9}\\\\2\frac{7}{12} - \frac{2}{3} : 8 + \frac{7}{8} = \frac{31}{12} - \frac{2}{3} * \frac{1}{8} + \frac{7}{8} = \frac{31}{12} - \frac{1}{12} + \frac{7}{8} = \frac{30}{12} + \frac{21}{24} = \frac{60}{24} + \frac{21}{24} = \frac{81}{24} = 3\frac{9}{24} = 3\frac{3}{8}\\[/tex]
[tex]1\frac{4}{5} - \frac{2}{3} : \frac{5}{4} = \frac{9}{5} - \frac{2}{3} : \frac{5}{4} = \frac{9}{5} - \frac{2}{3} * \frac{4}{5} = \frac{9}{5} - \frac{8}{15} = \frac{27}{15} - \frac{8}{15} = \frac{19}{15} = 1\frac{4}{15}[/tex]